2020
DOI: 10.3389/fneur.2020.00919
|View full text |Cite
|
Sign up to set email alerts
|

CSF Neurofilament Light Chain Elevation Predicts ALS Severity and Progression

Abstract: Objectives: This study compared neurofilament light chain (NFL) levels in the cerebrospinal fluid (CSF) of patients with sporadic amyotrophic lateral sclerosis (sALS) with levels in patients with other neurological diseases and healthy controls and assessed correlations between NFL levels and clinical indicators of sALS. Methods: We used enzyme-linked immunosorbent assays to determine the NFL levels in the CSF of 45 patients with sALS, 21 patients with other central nervous s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 34 publications
3
17
0
Order By: Relevance
“…Besides disease aggressiveness, three covariates exhibited statistically significant effects on CSF NfL levels of ALS patients. In accordance with previous studies, age showed a positive association with CSF NfL ( Vågberg et al, 2015 ; Gong et al, 2018 ; Steinacker et al, 2018b ; Sun et al, 2020 ). This most likely reflects the degenerative process in the brain associated with normal aging, which leads to a slowly progressive rise of neurofilaments in the CSF.…”
Section: Discussionsupporting
confidence: 92%
“…Besides disease aggressiveness, three covariates exhibited statistically significant effects on CSF NfL levels of ALS patients. In accordance with previous studies, age showed a positive association with CSF NfL ( Vågberg et al, 2015 ; Gong et al, 2018 ; Steinacker et al, 2018b ; Sun et al, 2020 ). This most likely reflects the degenerative process in the brain associated with normal aging, which leads to a slowly progressive rise of neurofilaments in the CSF.…”
Section: Discussionsupporting
confidence: 92%
“…In recent decades, several biomarkers in the body fluid, such as orexin, 8-Hydroxy-2′-Deoxyguanosine, peripheral proteasomes, caspases, dopamine, dopamine receptor, alpha-synuclein, and apolipoprotein A1 (ApoA1), have been suggested to be diagnostic of PD [ 11 ]; however, some of these biomarkers fail to reflect the disease course while others only exhibit vague results. Recently, significant aberration in neurofilament light chain (NfL) levels have been associated with Alzheimer’s disease (AD) [ 12 ], amyotrophic lateral sclerosis [ 13 ], multiple sclerosis [ 14 ] and cerebral vascular disease [ 15 ]. NfL, a 68 kDa neuronal cytoplasmic protein, is considered critical for radial growth and axon stability, and the release of NfL into blood and/or cerebrospinal fluid (CSF) circulation reflects axonal damage [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“… 73 Elevated CSF NfL is indicative of amyotrophic lateral sclerosis severity and progression. 74 Amongst neurodegenerative diseases, frontotemporal dementia and amyotrophic lateral sclerosis exhibit the greatest elevations in CSF NfL. 75 Compared to healthy controls, NfL levels are ∼20-fold higher in amyotrophic lateral sclerosis CSF, whereas they are 3-fold higher in frontotemporal dementia CSF.…”
Section: Neurofilament-related Biomarkersmentioning
confidence: 99%